Chronic viral hepatitis B and D in pregnant women: course and outcomes (review) - M. D. Akhmedova; Sh. A. Tashpulatova; G. A. Ikhtiyarova; M. T. Karimova (Журнал инфектологии)
Hepatitis B is most common among young people, which is explained by the ways of infection – parenteral, sexual and vertical. Mother-to-child transmission is the main route of infection for children in areas where the hepatitis B virus (HBV) is endemic.The available current data on the course and outcomes of chronic viral hepatitis B are contradictory in pregnant women. Some authors argue that the exacerbation of chronic hepatitis B is more common in the first and third trimesters in pregnant women, and with an increase in gestation, there is a deterioration in liver function and an increased risk of fulminant liver failure. Other researchers note a more severe course in the second half of pregnancy or in the first months after delivery.High replication of the virus increases the frequency of gestational diabetes mellitus, hemostatic disorders, the threat of termination of pregnancy, gestosis, fetoplacental insufficiency, risk of bleeding in childbirth, premature birth, untimely discharge of amniotic fluid, and the birth of premature babies.Children become chronic carriers of HBsAd in neonatal hepatitis. These findings suggest that transplacental infection before birth may be a mechanism contributing to higher rates of failed prevention in newborns born to women with a high viral load.We could not find data on the features of the course and outcomes of viral hepatitis D in pregnant women in the available sources,. At the same time, it is known that mixed infection is more severe.Polymorphisms of genes associated with the regulation of the state of the vascular wall can have a significant impact on the course of infection.The high prevalence of hepatitis D infection in different parts of the world indicates the need for a comprehensive study of this disease, followed by the development of special programs for the prevention, early diagnosis and treatment of hepatitis B and D in pregnant women.